Juridical Review of the Trade in Imported Used Clothing and Its Relationship to Consumer Protection Law (Case Study at Mangga Dua Shopping Center) - Fellicia Angelica Kholim; Angelia Angelia; Siti Amera Naelayara (CV. Rayyan Dwi Bharata, 2023)
Trade in used clothing imports (thrifting) uses a collection of goods that are no longer used, which are then traded and can be reused by other people. Apparently, this activity has a strong appeal for ordinary people who want to open a business. But in fact the sale of imported used clothing is contrary to Law Number 7 of 2014 concerning Trade, Minister of Trade Regulation (Permendag) Number 40 of 2022 concerning Amendments to Minister of Trade Regulation Number 18 of 2021 concerning Export Prohibited Goods and Import Prohibited Goods, and the Law Invite No. 8 of 1999 concerning Consumer Protection. However, in its existence, the public still views the activity of buying and selling imported used clothing products as quite promising, especially in terms of its economic nature and ignoring the legal consequences that may occur. Until finally, this phenomenon made the researchers want to study the trade practices of imported used clothing at the Mangga Dua Shopping Center. This study uses a research method that is used in the form of a juridical-empirical research method with the approach used is a statutory approach (Statute Approach) and a concept approach (Conceptual Approach) and the data source used is primary data by means of field research (Field Research).